1995
DOI: 10.1016/0735-1097(95)00292-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual-chamber pacing with a short atrioventricular delay in congestive heart failure: A randomized study

Abstract: Dual-chamber pacing with a short AV delay does not improve hemodynamic and clinical status or ejection fraction measured on the day after pacemaker implantation in patients with chronic congestive heart failure. Routine use of pacemaker therapy with a short AV delay aas a primary treatment of heart failure in patients without standard arrhythmic indications is unwarranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(81 citation statements)
references
References 45 publications
1
73
0
7
Order By: Relevance
“…The interest in conventional short AV delay DDD pacing in patients with heart failure waned as the result of a double-blinded randomized study that showed no immediate improvement in hemodynamics and no longterm change in ejection fraction or NYHA functional class. 11 With failure of conventional DDD pacing to show consistent improvement in hemodynamics in these patients, the interest has shifted to BV pacing.…”
Section: Dual Chamber Pacing As a Treatment Of Congestive Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The interest in conventional short AV delay DDD pacing in patients with heart failure waned as the result of a double-blinded randomized study that showed no immediate improvement in hemodynamics and no longterm change in ejection fraction or NYHA functional class. 11 With failure of conventional DDD pacing to show consistent improvement in hemodynamics in these patients, the interest has shifted to BV pacing.…”
Section: Dual Chamber Pacing As a Treatment Of Congestive Heart Failurementioning
confidence: 99%
“…[1][2][3] Today, dual chamber pacing is used only for the treatment of symptomatic bradyarrhythmias. On the other hand, preliminary results with biventricular (BV) pacing have shown improvement in New York Heart Association (NYHA) functional class and exercise tolerance in patients with depressed ejection fraction and intraventricular conduction delay.…”
mentioning
confidence: 99%
“…3 Although these results could not be reproduced in prospective studies 4,5 and improvements could only be demonstrated short-term in highly selected patients, 6 the race to find a pacing therapy for heart failure had begun. On the hypothesis that the disappointing results of dual-chamber pacing in prospective studies were due to cancelling or overcoming the beneficial effects of AV synchronisation by the adverse effect of RV pacinginduced dyssynchrony, 7,8 Cazeau and colleagues proposed a 4-chamber pacing mode and reported the first successful permanent implant in 1994.…”
Section: Crt: From Origins To Routine Clinical Practicementioning
confidence: 97%
“…Another significant reference is the DAVID Trial [9]. Several other papers appeared about dual-chamber pacing applied to congestive heart failure during the last decade of the former century; in fact and without expressly saying it, all aimed at correcting rightleft ventricular dyssynchrony, but mostly centering the criterion on the A-V delay [10][11][12][13][14][15][16][17][18][19]. Observe that the last reference comes from a multicenter clinical study, and it is over 17-years-old.…”
Section: Discussionmentioning
confidence: 99%